QUALITY OF POPULATION DOCUMENT PUBLISHING SERVICE OF MIGRATION CITIZENS AFFECTED BY CISUNDAWU TOLL PROJECT IN RANCAKALONG DISTRICT SUMEDANG REGENCY - Rika Kusdinar; Ramdani . (UNIVERSITAS PAKUAN, 2021)
This study aims to analyze problems regarding service quality, inhibiting factors of service quality, and efforts to improve the quality of service for publishing population documents in the integrated services section in Rancakalong District, Sumedang Regency. The method used in the preparation of this thesis is qualitative research methods. Data collection techniques are carried out through library research and field studies which include: observation, interviews, documentation study, and triangulation. The determination of the sample / informant in this study was carried out using purposive sampling. Furthermore, data analysis is carried out by referring to the technical analysis of the miles and Huberman models, namely: data reduction, data display, and conclusion drawing / verification (conclusion). Sources of data / informants in this study are: Head of Sub-District, Head of Sub-District Secretariat, Public Service Sub-Division, Head of General Subdivision, Assets and Administration, Governance Section. Based on the results of interviews, observations and documentation results, data analysis is then obtained that the quality of service for the publication of population documents at the service section of Rancakalong District, Sumedang Regency can be said to be quite good, it can be seen in the aspects of reliability, tangibles, responsiveness, assurance, and empathy. Although there are still obstacles that occur in the process of improving service quality, namely service procedures and service flows that not many people understand or have not been maximally socialized to the community. Efforts are made to overcome barriers to improving service quality, namely by the existence of effective communication, giving authority, giving motivation, training on services.